If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 4 + -1(8 + -1z) -6 = 4 + (8 * -1 + -1z * -1) -6 = 4 + (-8 + 1z) Combine like terms: 4 + -8 = -4 -6 = -4 + 1z Solving -6 = -4 + 1z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -6 + -1z = -4 + 1z + -1z Combine like terms: 1z + -1z = 0 -6 + -1z = -4 + 0 -6 + -1z = -4 Add '6' to each side of the equation. -6 + 6 + -1z = -4 + 6 Combine like terms: -6 + 6 = 0 0 + -1z = -4 + 6 -1z = -4 + 6 Combine like terms: -4 + 6 = 2 -1z = 2 Divide each side by '-1'. z = -2 Simplifying z = -2
| ln(x+4)-2lnx=5 | | 7a-3=2a-20 | | 6x+54=4x+70 | | (2x^2+5x-3)(2x+1)= | | 1-5+(-9)-7-13= | | 28x+13=9x+2 | | f(10)=3x+24 | | 28-12.12=s | | -3x+12y=36 | | 6u^2+3u-84=0 | | c-13=-5 | | x^2(4e^2x)+4x(2e^2x)-18(e^2x)=0 | | 1.8z-0.8z+7.4=-6.6 | | 7v+7.8= | | 0.1=9h | | X^4-9x^2+2=0 | | -8+(-1)= | | -8=-3(5-2x)+1 | | 2(3x-4)=8+2x+4 | | 4.3-1.4(p+7)=-9 | | 3z+3=15 | | 0.30x+0.30(40)=0.15(130) | | 3y-y=5 | | -2(1)-4(1.5)=6 | | 3(x+2)=-18+9x | | 10t+10.3= | | 3(10+6x)=84 | | (xy-x)dx+(xy+y)dy=0 | | (35x-35)(25x-40)=0 | | 11+5v+3v^2=0 | | -6u=48 | | 4y=-4.4 |